Temperature Monitoring of High-Speed Railway Bridges in Mountainous Areas. Issue 3 (3rd July 2018) - Dai, Gonglian; Tang, Yu; Liang, Jinbao; Yang, Linghao; Chen, Y. Frank
Abstract: Solar radiation and temperature can cause the deformation of high-speed railway bridges which has an obvious effect on the position of the rails and thus on passenger comfort, especially when the bridge spans a mountainous area. In this study, the temperatures of a track–bridge system and the deflections of the tall piers belonging to a high-speed railway line in China were monitored for over three years. By adopting extreme value theory and a time-series method, the temperatures and temperature gradients of structural components of the bridge were investigated in relation to time. The results show that the monitored temperatures can be broken down into the uniform temperature and the fluctuation temperature, which cause axial deformation and structural deflection, respectively. A uniform temperature curve was fitted using the Fourier series function and then used to calculate the axial deformations for different components of the track–bridge system over a one-year period. Additionally, the extreme temperature differences estimated for a 100-year return period can be used to encapsulate the maximum values of the daily temperature difference. Thus, the proposed temperature model can effectively estimate the structure's temperature-induced deformations.